Développement et territoires : une question d’environnement et de ressources territoriales ? - Eric Glon; Bernard Pecqueur (Territoire en Mouvement)
The text stress on the linkages between, in one hand, the process of building of “territories” which comes from the behaviour and the connexions between actors, stakeholders of the spatial dynamics and, in the other hand, the environmental resources. These resources must not be considered only like exogenous constraints but as cultural signals which areelements of the creation of the territories. The importance of the environmental resources emerge at an historical moment so called “post fordist” in a global world where the quality and the specificity of the production are crucial. The text is illustrated by two examples : Queen Charlotte Islands (C. B., Canada) and Metaleurop (Noyelles-Godault, North of France)